Os Potiguara da Baía da Traição e Montea-Mór: história, etnicidade e cultura - Palitot, Estevao Martins (2005)
This thesis concerns to an interpretation of the historical situations lived by the Potiguara Indian people, inhabitant of the north cost of Paraíba-Brazil. The elaboration of ethnic boundaries, the cultural production, the land occupation processes and the social organization are analyzed according to the constitution of an inter-social field determined by the historical presence of several agencies, generally groups of agro industries. industrials and the government that work to implant Indian policy. Our reflection is concentrated on the relational aspect and on interaction among the Potiguara Indians and the local society. In this way, we studied how the society of Paraíba considers the Indians. in order to draw a historical line of their social organization. Finally, we show how the lndians represent their ethnic and cultural specification to themselves and to the local society through such processes.